A Corpus-Based Study of Reformulation Markers: The Case of Native versus Non-Native Research Articles - Mohammad Alipour (Universitas Cokroaminoto Palopo, 2019)
This study presents a corpus-based study of reformulation markers as a common metadiscourse device in research articles of applied linguistics by native and Iranian non-native writers. Toward this end, qualitative and quantitative analyses of reformulation devices were conducted. The corpora were compiled by downloading articles from academic journals which were selected via convenience sampling. Each corpus included approximately one million words. All the analyses were conducted through employing Murillo’s (2004, 2007) classification which consists of three broad categories: explicit meaning functions (identification, specification, and explanation), conceptual meaning functions (definition and denomination), and implicit meaning functions (conclusion and mathematical operation). After analyzing the data, Chi-square tests were performed to determine whether the results found in the analysis were statistically significant. The results revealed that there were differences between the functions of reformulation markers (RMs) across research articles written by native and non-native writers. In particular, they differ in terms of their types and functions, where non-native writers of applied linguistics research articles (RAs) use RMs much more frequently than native writers of applied linguistics. In light of the findings, recommendations are made for EAP classes as well.